2014
DOI: 10.13080/z-a.2014.101.050
|View full text |Cite
|
Sign up to set email alerts
|

Dirvos paruošimo įtaka žolinių augalų vystymuisi miško želdiniuose žemės ūkiui naudotuose plotuose ir kirtavietėse

Abstract: The influence of soil preparation on the development of ground vegetation during the establishment of forest plantations was studied. It was found that in the first-year plantations on former farmland the least biomass of ground vegetation develops on furrows. Complete soil tillage to the depth of 22-27 cm, ploughed in berms or elimination of weeds with Roundup Bio may reduce the biomass of ground vegetation by up to two times. Soil ploughing in berms or piles always reduced the mass of weeds.In the second yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…However, the actual mean projective cover of ground vegetation before the tending was signifi cantly higher in spot-mounded sites in comparison to disc-trenched sites: 78 and 54%, respectively. Earlier studies in similar climatic conditions had found, that soil preparation method determines the shading of seedlings and thus the need for tending; the least shaded were seedlings planted on wide (100 cm) furrows and 30 cm high mounds (Suchockas et al, 2014). So both of the soil preparation methods analysed in our study can yield similar results in relation to vegetation competition.…”
Section: Tending In Relation To Soil Preparation Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…However, the actual mean projective cover of ground vegetation before the tending was signifi cantly higher in spot-mounded sites in comparison to disc-trenched sites: 78 and 54%, respectively. Earlier studies in similar climatic conditions had found, that soil preparation method determines the shading of seedlings and thus the need for tending; the least shaded were seedlings planted on wide (100 cm) furrows and 30 cm high mounds (Suchockas et al, 2014). So both of the soil preparation methods analysed in our study can yield similar results in relation to vegetation competition.…”
Section: Tending In Relation To Soil Preparation Methodssupporting
confidence: 75%
“…Similarly, grasses were the dominant ground vegetation type in second and third year after the clearcut in forest types on fertile soil also in Lithuania. Height of weeds were similar on ploughed berms and mounds (Suchockas et al, 2014). Grasses had been noted as most signifi cant competitors, capable to reduce height-growth of seedlings, primarily due to fast root growth and consequently intensive water uptake by graminoids (Coll et al, 2003).…”
Section: Tending In Relation To Soil Preparation Methodsmentioning
confidence: 98%
See 1 more Smart Citation